The Second Victim Experience of Nurses Involved in Medical Mistakes: Systematic Review of Referral Processes, Feasibility, and Effectiveness - Abuallah, Sanaa Nasser; Hady, Rana Shoai Ali; Hadi, Reem Shoue Ali; Dahish, Aisha Ali Yahia; Aqeel, Nazekh Mohammed Ibrahim; Khalil , Weaam Ali Abkar; Jawhar, Badriah Saleh Colaib; Hakami, Halima Muhammad Ali; Hakami, Sarah Mohammed Ali; Asiri, Ishraq Yahya Mohammed (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background: <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">The second victim syndrome is the intense emotional and professional damage caused to nurses by medical mistakes, but supporting mechanisms, particularly referral processes, are rudimentary. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">This review synthesizes evidence concerning referral processes among second victim nurses, examining their feasibility, limitations, and innovations to inform fair and effective support interventions. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods: <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">An integrative review was conducted searching PubMed, CINAHL, Scopus, and Web of Science (2000–2025) for peer-reviewed articles on second victim nurses. Forty sources, including qualitative, quantitative, and mixed-methods studies, were reviewed for themes of referral mechanisms, using thematic analysis and Joanna Briggs Institute appraisal instruments. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results: <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Referral automation happens in a mere 18% of organizations, with low awareness (74.8% unfamiliarity) and stigma as points of hindrance. Active models like MUHC's pager system and coordinated pathways bring rise to uptake, while innovations like the Talk to Me program achieve 100% uptake. Virtual programs externally (e.g., YANA) are 80% possible in under-resourced settings. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion: <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Proactive, just culture-based referral systems are crucial to enabling second victim nurses, preventing distress, and enhancing patient safety.